Human Cytomegalovirus-Encoded Receptor US28 Is Expressed in Renal Allografts and Facilitates Viral Spreading In Vitro. Issue 3 (March 2017) - Lollinga, Wouter T.; de Wit, Raymond H.; Rahbar, Afsar; Vasse, Gwenda F.; Davoudi, Belghis; Diepstra, Arjan; Riezebos-Brilman, Annelies; Harmsen, Martin C.; Hillebrands, Jan-Luuk; Söderberg-Naucler, Cecilia; van Son, Willem J.; Smit, Martine J.; et al.
Abstract : Background: Renal transplantation is the preferred treatment for patients with end-stage renal disease. Human cytomegalovirus (HCMV) activation is associated with decreased renal graft function and survival. Human cytomegalovirus encodes several immune modulatory proteins, including the G protein-coupled receptor US28, which scavenges human chemokines and modulates intracellular signaling. Methods: Our aim was to identify the expression and localization of US28 in renal allograft biopsies by immunohistochemistry and determine its role in viral spreading in vitro. Results: Immunohistochemistry revealed US28 in 31 of 34 renal transplant biopsies from HCMV-seropositive donors. Expression was independent of HCMV viremia or IgG serostatus. US28 was predominantly expressed in the cytoplasm of vascular smooth muscle cells (VSMCs) and tubular epithelial cells, with a median positivity of 20% and 40%, respectively. Also, US28-positive cells were present within arterial neointima. In contrast to US28, HCMV-encoded immediate early antigen was detected in less than 5% of VSMCs, tubular epithelial cells, interstitial endothelium, interstitial inflammatory infiltrates, and glomerular cells. Primary VSMCs were infected with green fluorescent protein–tagged wild type or US28-deficient HCMV. The viral spreading of US28-deficient HCMV, via culture medium or cell-to-cell transmission, was significantly impeded as shown by green fluorescent protein (ie, infected) cell quantification and quantitative real-time polymerase chain reaction. Additionally, the number and size of foci was smaller. Conclusions: In summary, HCMV-encoded US28 was detected in renal allografts from HCMV-positive donors independent of viremia and serostatus. Also, US28 facilitates HCMV spreading in VSMCs in vitro. Because the vasculature is affected in chronic renal transplant dysfunction, US28 may provide a potential target for therapeutic intervention. Abstract : CMV-encoded US28 is detected in VSMCs, arterial neointima and TECs of renal allografts from CMV-positive donors. US28 facilitates CMV spreading in VSMCs in vitro. US28 may provide a potential target for therapeutic intervention. Supplemental digital content is available in the text.